Effectiveness of employee branding and Youth initiatives at Nestlé Bangladesh Limited (NBL) - Tabassum, Faizava Nawshin (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.